2020
DOI: 10.1002/chem.202002192
|View full text |Cite
|
Sign up to set email alerts
|

Ru/CdS Quantum Dots Templated on Clay Nanotubes as Visible‐Light‐Active Photocatalysts: Optimization of S/Cd Ratio and Ru Content

Abstract: An anoarchitectural approachb ased on in situ formation of quantumd ots (QDs) within/outsidec lay nanotubes was developed. Efficient and stable photocatalysts active under visible light werea chieved with rutheniumdoped cadmium sulfide QDs templated on the surface of azine-modified halloysite nanotubes. The catalytic activity was tested in the hydrogen evolutionr eaction in aqueous electrolyte solutions under visible light. Ru doping enhanced the photocatalytic activity of CdS QDs thanks to better light absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Afterwards, this nanomaterial was used for Ru deposition (Figure 7). Starting from these findings the same authors in another work, doped the CdS NPs stabilized onto and into HNTs with Ru NPs to obtain a photocatalyst for hydrogen evolution [87]. To efficiently bind cadmium nitrate onto HNTs, the clay was first functionalized with azine as a chelating agent, and then the complex was treated with thioacetamide to finally achieve the CdS NPs supported onto HNTs (CdS/Halloysite).…”
Section: Hnts As Support For Metal Catalystmentioning
confidence: 99%
“…Afterwards, this nanomaterial was used for Ru deposition (Figure 7). Starting from these findings the same authors in another work, doped the CdS NPs stabilized onto and into HNTs with Ru NPs to obtain a photocatalyst for hydrogen evolution [87]. To efficiently bind cadmium nitrate onto HNTs, the clay was first functionalized with azine as a chelating agent, and then the complex was treated with thioacetamide to finally achieve the CdS NPs supported onto HNTs (CdS/Halloysite).…”
Section: Hnts As Support For Metal Catalystmentioning
confidence: 99%
“…Another positive feature of halloysite clay nanotubes is their biological and ecological biocompatibility. On the examples of heavy metal containing nanoparticles, it was shown that such systems possessed no acute toxicity to model cells and organisms [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to chemical composition, it is possible to selectively modify the HNTs surfaces leading to the development of different nanostructures. [10][11][12] HNTs have been used as catalysts, [13][14][15] materials for pollutant removal, [16][17] fillers for polymeric matrices 18 and often as drug carriers [19][20] and delivery systems. [21][22] In this context, one of the most promising feature of HNTs and modified HNTs, is their ability to penetrate the cellular membrane surrounding the cell nuclei.…”
Section: Introductionmentioning
confidence: 99%